School Development Strategy (Case Study at Kemala Bhayangkari Kindergarten School 02 Pabaeng-Baeng Brimob Sulawesi Selatan Branch) - Nurul Fuadi; Lahming; Andi Sukainah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The research aims to determine internal factors (strengths, weaknesses) and external factors (opportunities, threats) in improving the quality of Kemala Bhayangkari 02 Pabaeng-baeng Kindergarten School and to find out the strategies that need to be implemented to improve the quality of Kemala Bhayangkari 02 Pabaeng-baeng Kindergarten School based on SWOT analysis . This study uses a qualitative and quantitative approach with the SWOT analysis method. Data collection techniques are Observation interviews, questionnaires, and Documentations Data analysis techniques are descriptive analysis, SWOT matrix analysis, and IFE (internal factor evaluation) and EFE (external factor evaluation) matrix analysis. The results of the SWOT analysis of Kemala Bhayangkari Kindergarten School are in quadrant 1 where the IFE and EFE scores are (2.22: 1.38) which is a position that supports an aggressive strategy in improving school development. Based on the results obtained, the strategy that must be carried out to improve the quality of schools is the SO strategy (Strength-Opportunities strategy) which supports aggressive growth policies as the approach.